Diversity of Indian Barnacles in Marine Provinces and Ecoregions of the Indian Ocean - Trivedi, Jigneshkumar; Patel, Krupal; Chan, Benny K. K.; Doshi, Mahima; Padate, Vinay (Frontiers in Marine Science, 2021)
The present study is the first completed and taxonomically validated literature review on the biodiversity of barnacles (Cirripedia) in India. A total of 155 species belonging to 75 genera, 19 families were recorded in India. Maximum number of species were recorded from Bay of Bengal Province located on the eastern side of the Indian Peninsula, which composed of the Eastern India Ecoregion (76 species) and Northern Bay of Bengal Ecoregion (34 species). The West and South India Shelf Province has relatively lower number of species (Western India Ecoregion 29 species, South India and Sri Lanka Ecoregion, 40 species) when compared to the Bay of Bengal Province. The Andaman Province composed of the Andaman and Nicobar Islands, which contains 65 species. Most of the coral-associated barnacles (family Pyrgomatidae) were recorded in the Andaman and Nicobar Islands Ecoregion (7 species), Eastern India Ecoregion (6 species) and Northern Bay of Bengal Ecoregion (5 species), where these ecoregions contain coral reefs. Sponge associated barnacles (mostly in the subfamily Acastinae) were recorded in the Eastern India Ecoregion, Southern India and Sri Lanka and Andaman and Nicobar Island Ecoregions. Deep-water species were relatively extensively recorded in the Andaman and Nicobar Islands Ecoregion (21 species), followed by South India and Sri Lanka Ecoregion (9 species) and Eastern India Ecoregion (7 species). Six Atlantic/boreal cold water species previously reported in India were removed due to incorrect identification, and some incorrect identified species were validated and corrected.